Development of embodied capital: Diet composition, foraging skills, and botanical knowledge of forager children in the Congo Basin - Veen, Jorin; Jang, Haneul; Raubenheimer, David; van Pinxteren, Bryndan O. C. M.; Kandza, Vidrige; Meirmans, Patrick G.; van Dam, Nicole M.; Dunker, Susanne; Hoffmann, Petra; Worrich, Anja; Janmaat, Karline R. L. (Frontiers in Ecology and Evolution, 2023)
The embodied capital theory states that the extended juvenile period has enabled human foragers to acquire the complex foraging skills and knowledge needed to obtain food. Yet we lack detailed data on how forager children develop these skills and knowledge. Here, we examine the seasonal diet composition, foraging behavior, and botanical knowledge of Mbendjele BaYaka forager children in the Republic of the Congo. Our data, acquired through long-term observations involving full-day focal follows, show a high level of seasonal fluctuation in diet and foraging activities of BaYaka children, in response to the seasonal availability of their food sources. BaYaka children foraged more than half of the time independent from adults, predominantly collecting and eating fruits, tubers, and seeds. For these most-consumed food types, we found an early onset of specialization of foraging skills in children, similar to the gendered division in foraging in adults. Specifically, children were more likely to eat fruit and seed species when there were more boys and men in the group, and girls were more likely than boys to collect tuber species. In a botanical knowledge test, children were more accurate at identifying plant food species with increasing age, and they used fruits and trunks for species identification, more so than using leaves and barks. These results show how the foraging activities of BaYaka children may facilitate the acquisition of foraging skills and botanical knowledge and provide insights into the development of embodied capital. Additionally, BaYaka children consumed agricultural foods more than forest foods, probably reflecting BaYaka’s transition into a horticultural lifestyle. This change in diet composition may have significant consequences for the cognitive development of BaYaka children.